Modern concrete materials binders, additions and admixtures : proceedings of the international conference held at the University of Dundee Scotland, UK on 8-10 September 1999 - Dhir, Ravindra K.; Dyer, Thomas D. (Thomas Telford, 1999)
Topics discussed in 'Modern Concrete Materials' include the modelling of binder performance, the use of by-product materials, the development of novel admixture formulations, and the optimisation of concrete performance.